Sequential oxidation of Jasmonoyl-Phenylalanine and Jasmonoyl-Isoleucine by multiple cytochrome P450 of the CYP94 family through newly identified aldehyde intermediates. (September 2015) - Widemann, Emilie; Grausem, Bernard; Renault, Hugues; Pineau, Emmanuelle; Heinrich, Clément; Lugan, Raphaël; Ullmann, Pascaline; Miesch, Laurence; Aubert, Yann; Miesch, Michel; Heitz, Thierry; Pinot, Franck
Graphical abstract: Members of the CYP94 family catalyze the production of oxidized derivatives of Jasmonoyl-Phenyalanine which accumulates in Arabidopsis leaves infected by Botrytis cinerea . Highlights: Metabolite profiling by UPLC-MS/MS shows JA-Phe accumulation in stressed Arabidopsis leaves. Members of the CYP94 family have the catalytic capabilities to oxidize JA-Phe in vitro . Studies of loss- and gain-of-function plant lines showed involvement of CYP94s in JA-Phe clearance. Aldehyde derivative of JA-Ile is formed in planta after leave wounding. Abstract: The role and fate of Jasmonoyl-Phenylalanine (JA-Phe), an understudied conjugate in the jasmonate pathway remain to be unraveled. We addressed here the possibility of JA-Phe oxidative turnover by cytochrome P450s of the CYP94 family. Leaf wounding or fungal infection in Arabidopsis resulted in accumulation of JA-Phe, 12-hydroxyl (12OH-JA-Phe) and 12-carboxyl (12COOH-JA-Phe) derivatives, with patterns differing from those previously described for Jasmonoyl-Isoleucine. In vitro, yeast-expressed cytochromes P450 CYP94B1, CYP94B3 and CYP94C1 differentially oxidized JA-Phe to 12-hydroxyl, 12-aldehyde and 12-carboxyl derivatives. Furthermore, a new aldehyde jasmonate, 12CHO-JA-Ile was detected in wounded plants. Metabolic analysis of CYP94B3 and CYP94C1 loss- and gain-of-function plant lines showed that 12OH-JA-Phe was drastically reduced in cyp94b3 but not affected in cyp94c1, while single or double mutants lacking CYP94C1 accumulated less 12COOH-JA-Phe than WT plants. This, along with overexpressing lines, demonstrates that hydroxylation by CYP94B3 and carboxylation by CYP94C1 accounts for JA-Phe turnover in planta . Evolutionary study of the CYP94 family in the plant kingdom suggests conserved roles of its members in JA conjugate homeostasis and possibly in adaptative functions. Our work extends the range and complexity of JA-amino acid oxidation by multifunctional CYP94 enzymes in response to environmental cues.